2020
DOI: 10.1186/s43014-020-00026-w
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of germination and probiotic fermentation on underutilized cereal and millet grains

Abstract: Cereals and millets have been known as poor man’s crops for a long time, and have good potential in the mercenary system of food and in research and development but these coarse grains have been leftover and underutilised since a long time. In addition to nutritional properties, various elements of cereal grains contain phenolic compounds as well as various anti-nutritional factors. To improve the nutritional quality and availability of these grains, they are processed in several ways. This review discusses th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 92 publications
0
28
0
Order By: Relevance
“…In general, the germination process is known to decrease the concentration of antinutrients in the resulting sprouts. This has been extensively highlighted in the literature for many different species, i.e., green gram, cowpea, lentil and chickpea [256,257], buckwheat [258], quinoa [259], millet [260,261] barley [262], and flaxseeds [263]. In particular, Pal et al [264] compared the effects of germination, dehulling, and cooking in horse gram, and showed different patterns of nutrient/antinutrient ratios in relation to treatments.…”
Section: Antinutrients and Allergens In Sproutsmentioning
confidence: 99%
“…In general, the germination process is known to decrease the concentration of antinutrients in the resulting sprouts. This has been extensively highlighted in the literature for many different species, i.e., green gram, cowpea, lentil and chickpea [256,257], buckwheat [258], quinoa [259], millet [260,261] barley [262], and flaxseeds [263]. In particular, Pal et al [264] compared the effects of germination, dehulling, and cooking in horse gram, and showed different patterns of nutrient/antinutrient ratios in relation to treatments.…”
Section: Antinutrients and Allergens In Sproutsmentioning
confidence: 99%
“…Lipid hydrolysis (Choudhury et al, 2011) during germination was also taken as a possibility, in view of the results of Annor et al (2013), who found an increase in starch digestibility when samples were defatted. Germination followed by fermentation appeared to be more effective in improving protein and starch digestibility than germination alone (Budhwar et al, 2020). Thus, germination followed by fermentation could offer a unique option from a nutritional point of view, making starch and protein in millets more digestible.…”
Section: Proteinsmentioning
confidence: 99%
“…Kouakou et al (2008), showed that because of the consumption of carbohydrates for F I G U R E 3 Flow diagram for Processing of millet by germination respiration during the germination process, as a consequence, there was a significant increase in the protein content in millets. Budhwar et al (2020), reported that an increase in the total protein content in finger millet during germination was due to an increase in enzymatic activity. Furthermore, this study also showed that time intervals given for germination played a vital role in affecting various changes.…”
Section: Proteinsmentioning
confidence: 99%
“…One of the potentially manageable foods for developing an effective synbiotic food system can be cereal grains, which offer the positive benefits of combining probiotic species with whole grains that may serve as a staple prebiotic substance. Recent studies indicate that certain probiotic microorganisms contain necessary components to be established as synbiotic food, for instance, cereal-based efficient products (Budhwar et al, 2020). Additionally, the usage of certain microorganisms as beginning cultures throughout the food fermentation process is a notably favorable technique to improve the taste and mineral bioavailability in native cerealbased fermented foods (Nkhata et al, 2018;Ogunremi et al, 2020).…”
Section: Future Perspectives In Developing Effective Synbiotic Food Incorporating the Probiotic Bacillimentioning
confidence: 99%
“…The preparation of cereals with advanced approaches creates an enhanced nutrient platform with a preferred amino acid pattern. Fermentation is considered an essential and accepted method, significantly decreasing the antinutrients existing in coarse cereals such as trypsin inhibitor, phytic acid, and tannins (Budhwar et al, 2020). Phytase activity is a beneficial technological characteristic in LAB proposed to be administered FIGURE 2 | The conceptual idea for developing synbiotic food system through facilitating survivability of probiotic cells and inducing production of health promoting functional molecules.…”
Section: Future Perspectives In Developing Effective Synbiotic Food Incorporating the Probiotic Bacillimentioning
confidence: 99%